Exploring Kerr and McKay’s Beehive of Smart Girls: Understanding the Challenges Facing Gifted Adolescent Females - Guthrie, Kate H. (Gifted child today magazine, 2020)
For gifted girls, the journey toward self-actualization can be particularly challenging during adolescence. To better support gifted adolescent girls, this article explores a contemporary framework for understanding smart girls of the 21st century: Kerr and McKay’s beehive of smart girls. Kerr and McKay’s typology highlights how different combinations of characteristics ultimately create rich variations of gifts and talents—instead of assuming all smart girls have the same characteristics, experiences, and visions. Building on their framework, this article (a) offers additional insights into how each type of smart girl may experience gifted adolescence, (b) suggests potential barriers to self-actualization each type of smart girl may face, and (c) invites voices of educators from middle and high school classrooms to share their own reflections and insights of how they have come to know each type of smart girl.